The Young Kyai (Lora) and Transformation of the Pesantren in Madura - Umiarso El-Rumi (Islam Realitas: Journal of Islamic and Social Studies, 2020)
This research focuses on the leadership of the A’wam Council, group of young religious scholars or kyai (Lora) at the Mambaul Ulum Bata-Bata Pamekasan Madura Islamic Boarding School, in carrying out institutional transformation of the pesantren (traditional Islamic boarding schools). As the protector of religious-culture, Lora not only preserves the various acpects of religion such as marriage and security (by performing the rituals of tahlil, or yasinan) but also maintains public morality and good social and political relations in the community. Lora functions as the a protector of culture and religion (amanah or public trust) in order to increase the social capital of the pesantren (enriching social networks). Using the collective leadership theory by O’Neill & Berinkerhoff and a qualitative approach through observation, interviews, and documentation, this article finds that Lora leadership made use of Islamic values in transforming this institution from a traditional pesantren (salaf) to modern one (khalaf). This process was coupled with the development of an interconnective-integralist paradigm that led to a new pesantren model that not only preserves the traditional methods but also adopted new developments in contemporary thought, namely combining and integrating religious knowledge with general science Riset ini memfokuskan pada dinamika kepemimpinan Dewan A’wam –yang merupakan kumpulan kyai muda (Lora) di Pesantren Mambaul Ulum Bata-Bata Pamekasan Madura- dalam melakukan transfomasi kelembagaan pesantren. Sebagai pelindung budaya-agama, Lora tidak hanya memposisikan diri untuk menjaga berbagai dimensi agama seperti pernikahan dan keselamatan (tahlil, atau yasinan), namun juga menjaga moralitas budaya masyarakat serta dinamika sosial politik. Konsistensi dalam peran sebagai pelindung budaya-agama difungsikan oleh Lora untuk menumbuhkan modal sosial pesantren (amanah dan jejaring sosial). Dengan menggunakan teori kepemimpinan kolektif oleh O’Neill & Berinkerhoff dan pendekatan kualitatif melalui observasi, wawancara, dan dokumtasi, artikel ini menemukan bahwa kepemimpinan Lora didasarkan pada nilai-nilai religius Islam di dalam melakukan pengelolaan pesantren hingga mampu bertransformasi dari pesantren tradisional (salaf) ke modern (khalaf). Proses tersebut dirangkai dengan perkembangan paradigma interkonektif-integralis yang berimplikasi pada model pesantren yang hanya mengajarkan ilmu agama akan diganti dengan nuansa baru, yaitu memadukan dan mengintegrasikan ilmu agama dengan ilmu umum